Evaluation of nucleic acid-based test (PACE 2C) for simultaneous detection of Chlamydia trachomatis and Neisseria gonorrhoeae in endocervical specimens. - Iwen, P C (1995)
A nucleic acid-based test (Gen-Probe PACE 2C System) was evaluated for the ability to detect Chlamydia trachomatis and Neisseria gonorrhoeae from endocervical specimens in a single assay. Three swab samples, randomized for collection order, were obtained from each patient and tested by N. gonorrhoeae and C. trachomatis culture and by the PACE 2C probe assay. Fifty of 395 specimens were culture positive for N. gonorrhoeae (17 specimens), C. trachomatis (26 specimens), or both (7 specimens), of which PACE 2C testing detected 48 specimens. The PACE 2C assay was positive for 56 specimens, including 8 specimens not positive by culture. Of the total of 10 discrepancies between culture and PACE 2C results, resolution testing yielded four false-negative culture, four false-positive PACE 2C, and two false-negative PACE 2C results. The sensitivity, specificity, and positive and negative predictive values for PACE 2C after reevaluation were 96.3, 98.8, 92.9 and 99.4%, respectively. The overall sensitivities for C. trachomatis and N. gonorrhoeae culture were 89.2 and 88.9%, respectively. The prevalence rate for C. trachomatis was 9.4%, and that for N. gonorrhoeae was 6.8%. The Gen-Probe PACE 2C System is a reliable alternative for screening endocervical specimens for both C. trachomatis and N. gonorrhoeae in a single assay.